Exploring Compound Words and Acronyms Used in Health Column of CNN International News - Fatimah, Siti; Ramadhina, Retno; Isminarni, Siti (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2025)
This research mainly aims to find out the types of compound words and acronyms found in CNN International news articles in the health column, which consists of 5 news articles. A descriptive qualitative method is used in this research to analyze the data. This research uses the theory from McCarthy (2002), regarding the types of compound words and the theory from Lieber (2009), regarding acronyms. The results of this research show that there are 3 types of compound words and their meanings consisting of compound verbs, compound adjectives, and compound nouns. Compound verb patterns: verb+verb, preposition+verb, compound adjective patterns: noun+adjective, adjective+adjective, verb+adjective, and compound noun patterns: verb+noun, noun+noun, adjective+noun, preposition+noun. This reseach also found acronyms used in 5 CNN International health column news.